Abca12-mediated lipid transport and Snap29-dependent trafficking of lamellar granules are crucial for epidermal morphogenesis in a zebrafish model of ichthyosis - Qiaoli Li; Michael Frank; Masashi Akiyama; Hiroshi Shimizu; Shiu-Ying Ho; Christine Thisse; Bernard Thisse; Eli Sprecher; Jouni Uitto (The Company of Biologists, 2011)
SUMMARY Zebrafish (Danio rerio) can serve as a model system to study heritable skin diseases. The skin is rapidly developed during the first 5-6 days of embryonic growth, accompanied by expression of skin-specific genes. Transmission electron microscopy (TEM) of wild-type zebrafish at day 5 reveals a two-cell-layer epidermis separated from the underlying collagenous stroma by a basement membrane with fully developed hemidesmosomes. Scanning electron microscopy (SEM) reveals an ordered surface contour of keratinocytes with discrete microridges. To gain insight into epidermal morphogenesis, we have employed morpholino-mediated knockdown of the abca12 and snap29 genes, which are crucial for secretion of lipids and intracellular trafficking of lamellar granules, respectively. Morpholinos, when placed on exon-intron junctions, were >90% effective in preventing the corresponding gene expression when injected into one- to four-cell-stage embryos. By day 3, TEM of abca12 morphants showed accumulation of lipid-containing electron-dense lamellar granules, whereas snap29 morphants showed the presence of apparently empty vesicles in the epidermis. Evaluation of epidermal morphogenesis by SEM revealed similar perturbations in both cases in the microridge architecture and the development of spicule-like protrusions on the surface of keratinocytes. These morphological findings are akin to epidermal changes in harlequin ichthyosis and CEDNIK syndrome, autosomal recessive keratinization disorders due to mutations in the ABCA12 and SNAP29 genes, respectively. The results indicate that interference of independent pathways involving lipid transport in the epidermis can result in phenotypically similar perturbations in epidermal morphogenesis, and that these fish mutants can serve as a model to study the pathomechanisms of these keratinization disorders.